Materials for a Social History of the Dutch Language in Medieval Britain: Three Case Studies from Wales, Scotland, and England. (4th May 2021) - Putter, Ad
ABSTRACT: This article presents some of the evidence we have for spoken and written Dutch in medieval Britain. It presents three case studies from Wales, Scotland, and England respectively. In Wales, the existence of a Dutch-speaking colony in Pembrokeshire is well known, but this article documents Dutch words both in the medieval writings of Gerald of Wales and in the modern dialect. In Scotland, I focus on a copy of a Dutch letter by Wouter Michiels and discuss the language and the identity of Michiels. In England, I focus on the remarkable quadralingual manuscript of the Book of Privileges. I conclude by pointing to the existence of other fascinating sources for the social history of Dutch in medieval Britain.